PENGARUH IDENTITAS PROFESIONAL, LOCUS OF COMMITMENT, DAN INTENSITAS MORAL TERHADAP INTENSI AUDITOR UNTUK MELAKUKAN TINDAKAN WHISTLEBLOWING (STUDI KASUS PADA KANTOR AKUNTAN PUBLIK SUMATERA BAGIAN SELATAN) - Muhammad Iqbal; Mukhtaruddin Mukhtaruddin; Abu Kosim (AKUNTABILITAS, 2018)
The purpose of this study was to obtain empirical evidence of the influence of professional identity, locus of moral commitment and intensity on intense auditor to perform an action whistleblowing. This study uses the concept of Theory of Planned Behavior as a theoretical basis. The population in this study is the auditor who worked on a public accounting firm in Southern Sumatra. The sampling technique in this study using a convenience sampling method. Results showed that the variables professional identity and locus of commitment not significant. While the variable intensity of the moral influence significant effect.